The Art of Frederick Remington ([S.l.] Master Vision, 1987)
It presents a brief biography of Frederick Remington and his works.
Narrators, James Dukas, Fred Burrel.
Keywords: Remington, Frederick; Equestrian statutes; Frontier and pioneer life in art